Sons and Lovers - Lawrence, D. H. 1885-1930 (Cambridge University Press, 2013)
Born within walking distance of ten Nottinghamshire pits, David Herbert Lawrence (1885–1930) was painfully aware that his frail physique and quiet character were ill suited to the mining industry upon which his community depended. The difficulties of his youth are manifest in Sons and Lovers, his first major novel and an insider's portrayal of the culture of the collieries. Writing to a friend, Lawrence explained the seed of his plot: 'a woman of character and refinement goes into the lower class, and has no satisfaction in her own life'. Stemming from this are the intricate difficulties in the relationships of Paul Morel, the second son of this unhappy mother, torn between her overpowering influence and two vastly different women - the quiet, old-fashioned Miriam and the modern divorcee Clara. Although initially deemed indecent and rejected for publication, Sons and Lovers appeared for the first time in 1913
Originally published in New York by Mitchell Kennerley in 1913
Keywords: Working class families / Fiction; Young men / Fiction; England / Fiction; Fiktionale Darstellung